Wireless soft tactile sensor array for interactive sensing 2.0 - Xiong, Yan (Nanyang Technological University, 2022)
This project looks at the design of a wireless soft tactile sensor array platform which include transistor based sensors, readout circuit and user application program. The transistor based sensor will be provided. The student need to develop a user interface for signal acquisition and display.